Hamburger Hill [videorecording (DVD)] - MacDonald, Peter, 1939-; Tanner, Peter, 1914-2002; West, Tegan; Vance, Courtney B.; Swerdlow, Tommy; Quill, Timothy Patrick; O'Shea, Daniel; O'Reilly, Harry; Nickles, Michael A., 1968-; McDermott, Dylan; James, Don (Actor); Dolan, Michael, 1965-; et al. (Lions Gate Entertainment, 2007)
Fourteen American soldiers in Vietnam battle for a mud-covered mound of earth that chews up soldiers like meat. They are fighting for their country, their fellow soldiers and their lives. War is hell, but this is worse.